Célébration et sainteté le Lévitique - Vogels, Walter 1932- (Paris Les Éditions du Cerf, 2015)
Notes bibliogr. p. [259] - 260
Includes bibliographical references (pages 259-260)
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Commentaries; Bible -- Commentaries; Bible, A.T, Lévitique; Holiness -- Biblical teaching; Holiness -- Biblical teaching; Kommentar